Development of a method for preparing octreotide derivative for diagnosis of neuroendocrine tumors - M. S. Larkina; E. V. Podrezova; O. D. Bragina; E. A. Tagirova; V. I. Chernov; M. S. Yusubov; E. A. Nesterov; V. S. Skuridin; S. V. Krivoshchekov; E. A. Yanovskaya; R. V. Gurto; M. V. Belousov (Бюллетень сибирской медицины)
Currently the development of technologies for labeling somatostatin with technetium-99m for diagnosing radionuclide neuroendocrine tumors is under way. Somatostatin analogues are binded with technetium99m only by the preliminary addition of a chelating agent. Therefore, it is important to develop a method for preparation of an octreotide derivative by modifying octreotide with precursors: ligands with high chelating ability for its tight binding with technetium-99m. ω-Bis(pyridin-2-ylmethyl)amino)aliphatic acids can be used successfully as such precursors.The purpose of the study was to develop a method for obtaining a new octreotide derivative for diagnosing neuroendocrine tumors.Materials and methods. The somatostatin octreotide analogue was used as the object of the study; succinimid-1-yl 6-(bis(pyridin-2-ylmethyl)amino)hexanoate was used as a chelating agent. Methods of high performance liquid chromatography and mass spectrometry were used to separate and analyze the synthesized compounds.Results. A method to produce an original octreotide derivative using a succinimid-1-yl 6-(bis(pyridin2-ylmethyl)amino)hexanoate as a chelating agent was proposed. The conditions of analytical and semipreparative HPLC for the analysis and purification of the active octreotide derivative (a monosubstituted derivative of the amino acid residue of D-phenylalanine) were suggested.Conclusion. The synthesized derivative of octreotide has a chelating center for strong binding to technetium-99m in its structure, which can be useful for diagnosing neuroendocrine tumors.